Structural Reforms and Economic Performance in Advanced and Developing Countries - Ostry, Jonathan; Prati, Alessandro; Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 2009)
This volume examines the impact on economic performance of structural policies-policies that increase the role of market forces and competition in the economy, while maintaining appropriate regulatory frameworks. The results reflect a new dataset covering reforms of domestic product markets, international trade, the domestic financial sector, and the external capital account, in 91 developed and developing countries. Among the key results of this study, the authors find that real and financial reforms (and, in particular, domestic financial liberalization, trade liberalization, and agricultural liberalization) boost income growth. However, growth effects differ significantly across alternative reform sequencing strategies: a trade-before-capital-account strategy achieves better outcomes than the reverse, or even than a "big bang"; also, liberalizing the domestic financial sector together with the external capital account is growth-enhancing, provided the economy is relatively open to international trade. Finally, relatively liberalized domestic financial sectors enhance the economy's resilience, reducing output costs from adverse terms-of-trade and interest-rate shocks; increased credit availability is one of the key mechanisms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet